Influence of Screen Time on Elementary Students' Social Activiaaazties: A Quantitative Study on Grade 6 Students' Participation in Sports and Scouting - Angie Rose J. Namocot; Maya Aulia Shahwah Dina; Ahmad Rizqi Wahyudi; Hakimi Affandi; Nenden Permas Hikmatunisa; Ari Syahidul Shidiq (Universitas Sebelas Maret, 2024)
This quantitative study investigates the impact of screen time on social activities among primary school students, specifically focusing on Grade 6 students' participation in sports and scouting. In an era dominated by digital technology, concerns have been raised regarding the potential effects of increased screen time on the physical and social development of children. To address this issue, the study employs a quantitative research approach, examining the relationship between screen time duration and involvement in traditional extracurricular activities. A sample of 116 Grade 6 pupils is selected for the study from the Philippines, Indonesia, and Malaysia, using a quota sampling method. A survey questions is utilized for data collection. Through rigorous data analysis, the study aims to draw evidence-based conclusions regarding the influence of screen time on social activities. The findings are can provide insights for parents, educators, and policymakers, shedding light on the complex relationship between digital technology usage and traditional extracurricular involvement. In the end, the study ultimately seeks to contribute practical recommendations to promote a balanced and healthy lifestyle for young learners in the digital age. By addressing potential negative effects of excessive screen time on students' participation in essential social and physical activities, the research aims to guide strategies for a more wholesome educational experience during their school years